2009
DOI: 10.1096/fj.09-131607
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase 2β as a novel enhancer of activin‐like receptor‐1 signaling

Abstract: ALK-1 is a transforming growth factor beta (TGF-beta) superfamily receptor that is predominantly expressed in endothelial cells and is essential for angiogenesis, as demonstrated by the embryonic lethal phentoype when targeted for deletion in mice and its mutation in the human disease hereditary hemorrhagic telangiectasia. Although ALK-1 and the endothelial-specific TGF-beta superfamily coreceptor, endoglin, form a heteromeric complex and bind similar TGF-beta superfamily ligands, their signaling mechanisms re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 53 publications
6
14
0
Order By: Relevance
“…Although BMP-9 can also bind ALK1, we observed no ALK1-induced enhancement of capillary stability or Akt activity in endoglin-null systems (Figures 1B and 3C). This finding is consistent with our previous report that increased ALK1 signaling antagonizes endothelial capillary sprouting (Lee et al., 2009). On the basis of these results, we propose a model (Supplemental Figure S3D) in which endoglin binds BMP-9 independent of ALK1 and ALK5 to preferentially promote PI3K/Akt activation after membrane recruitment.…”
Section: Discussionsupporting
confidence: 94%
“…Although BMP-9 can also bind ALK1, we observed no ALK1-induced enhancement of capillary stability or Akt activity in endoglin-null systems (Figures 1B and 3C). This finding is consistent with our previous report that increased ALK1 signaling antagonizes endothelial capillary sprouting (Lee et al., 2009). On the basis of these results, we propose a model (Supplemental Figure S3D) in which endoglin binds BMP-9 independent of ALK1 and ALK5 to preferentially promote PI3K/Akt activation after membrane recruitment.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, either shifting the balance of Smad1/5/8 and Smad2 signalling towards Smad1/5/8, or selectively increasing Smad1/5/8 signalling, is predicted to result in decreased endothelial cell migration. These results are consistent with our previous findings in which endoglin/GIPC , constitutively activated ALK1, or expression of the ALK1 activator, CK2b (Lee et al, 2009), increased Smad1/5/8 signalling and inhibited endothelial migration. The mechanisms by which these diverse factors might coordinate to regulate TGF-b superfamily signalling and endothelial cell function are currently being explored.…”
Section: Discussionsupporting
confidence: 93%
“…It was shown that CK2b specifically interacts with Alk-1 and by this interaction enhances Alk-1 signalling. This finally results in an inhibition of endothelial cell migration [53]. These functions of CK2b are consistent with its binding to and regulation of other serine/threonine kinases including Mos [54], A-raf [55] and Chk-1 [56].…”
Section: Ck2 and Angiogenesissupporting
confidence: 66%